Pancreatic cancer in liquid-based cytology: cytological features and cell block utility from 254 fine-needle aspiration samples - Jaeyong Min; Wookjin Oh; Baek-hui Kim (Journal of Pathology and Translational Medicine, 2025)
Background Despite the increasing use of liquid-based cytology (LBC) for pancreatic cancer diagnosis, relatively few studies have directly examined such research. This study analyzed the cytopathological features of pancreatic cancer in LBC and demonstrated the utility of cell blocks in diagnosing pancreatic lesions. Methods A retrospective review identified LBC from 254 pancreatic fine-needle aspirations (FNAs) (221 patients). FNAs were categorized into five subgroups based on cytopathological, clinical, and histopathological findings. Two pathologists evaluated cytological features in LBC samples, cell blocks, and tissue slides. Comparative analysis assessed differences between groups. Results Compared to benign lesions, LBC of pancreatic cancer more frequently showed a necrotic background, intermediate to high cellularity, mixed architecture, nuclear/cytoplasmic ratio >0.8, anisonucleosis >4:1, irregular and thick nuclear membranes, multinucleated tumor cells, hyperchromatic nuclei, coarse to clumped chromatin, and a prominent single nucleolus. In cases of conventional pancreatic ductal adenocarcinoma, the palliative treatment subgroup showed a higher incidence of necrotic background than the resection subgroup. In the cell block analysis, tumor cells not identified in LBC slides were detected in 16 FNAs. Additionally, 13 FNAs contributed to differential diagnosis: ancillary tests aided diagnosis in 12 FNAs, while histopathological evaluation of the cell block slide alone was helpful in one case. Conclusions The cytological features of pancreatic cancer in LBC are similar to those observed in conventional smears, with a necrotic background suggesting advanced (unresectable) disease. The cell block methodology minimizes tumor cell loss and facilitates differential diagnosis by enabling ancillary testing.